Electrochemotherapy with cisplatin of breast cancer tumor modules in a male patient - Reberšek, Martina (Radiology and oncology (Ljubljana), 2000)
Background. The metastases of breast cancer in a male patient were treated with electrochemotherapy by intratumoral injection of cisplatin. Electrochemotherapy is chemotherapy with the subsequent local application of electric pulses to the tumor nodules in order to increase drug delivery into the cells. Case report. Cutaneous metastases of breast cancer were treated with the intratumoral administration of cisplatin and by 8 electric pulses (1300 V/cm) applied a minute later to each cutaneous metastasis. The treatmentresulted in complete response of two electrochemotherapy treated cutaneous metastases and partial response of the third metastasis. In cutaneous metastases treated with intratumoral administartion of cisplatin without electric pulses, only partial response was obtained. Conclusion. This study confirms that electrochemotherapy with cisplatin is effective in the treatment of breast cancer metastases, too, as it was already proved for electrochemotherapy with bleomycin.
Keywords: Breast neoplasms, male; Cisplatin; dojke; Drug delivery systems; Drug therapy; Electroporation; rak (medicina); Therapy; zdravljenje